ANALISIS PENGARUH EPS, ROE, DER, DAN CR TERHADAP HARGA SAHAM DENGAN PER SEBAGAI VARIABEL MODERATING (Studi Kasus Pada Saham Indeks LQ45 Periode 2013-2015 yang Terdaftar Pada Bursa Efek Indonesia) - Aprillia Nur Choiriah; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstrakThe purpose of this research are : 1) to examine and analyzing of the EarningPer Share (EPS), Return On Equity (ROE), Debt To Equity Ratio (DER), Current Ratio (CR)to share price at LQ 45 company listed in Bursa Efek Indonesia , 2) to examine andanalyzing the relationship of Price Earning Ratio (PER) in moderating the relationshipbetween Earning Per Share (EPS), Return On Equity (ROE), Debt To Equity Ratio (DER),Current Ratio (CR) with share price at LQ 45 listed company On the Indonesia StockExchange. To obtain valid results, sampling technique used in this study is purposivesampling method so that obtained a sample of 61 companies . Data analysis methods usedwere multiple linear regression analysis, correlation analysis, classical assumption test(multicolinearity test, normality test, autocorrelation test, heterokedastisity test), hypothesistest using partial test (t test) and simultaneous test (f test).Using sample of LQ45 company listed in Indonesian Stock Exchange for theperiod of 2013-2015, the result of the research shows that Earning Per Share (EPS) has asignificant positive effect on stock price, Return on Equity (ROE) has positive effect to shareprice, Debt To Equity Ratio DER) has a negative effect on stock prices, Current Ratio (CR)has a positive effect on stock prices, and Price Earning Ratio (PER) moderates therelationship between Earning Per Share (EPS), Return On Equity (ROE), Debt To EquityRatio (DER) , Current Ratio (CR) with stock price.Keywords : Stock Price, Earning Per Share (EPS), Return On Equity (ROE), Debt To EquityRatio (DER), Current Ratio (CR), and Price Earning Ratio (PER).